Effects of single-walled carbon nanotubes on the bioavailability of PCBs in field-contaminated sediments. Issue 1 (August 2014) - Parks, Ashley N.; Chandler, G. Thomas; Portis, Lisa M.; Sullivan, Julia C.; Perron, Monique M.; Cantwell, Mark G.; Burgess, Robert M.; Ho, Kay T.; Ferguson, P. Lee
Abstract Adsorption of hydrophobic organic contaminants (HOCs) to black carbon is a well-studied phenomenon. One emerging class of engineered black carbon materials are single-walled carbon nanotubes (SWNTs). Little research has investigated the potential of SWNT to adsorb and sequester HOCs in complex environmental systems. This study addressed the capacity of SWNT, amended to polychlorinated biphenyl (PCB)-contaminated New Bedford Harbor (NBH) sediment, to reduce the toxicity and bioaccumulation of these HOCs to benthic organisms. Overall, SWNT amendments increased the survival of two benthic estuarine invertebrates, Americamysis bahia and Ampelisca abdita, and reduced the accumulation of PCBs to the benthic polychaete, Nereis virens. Reduction in PCB bioaccumulation by SWNT was independent of Kow. Further, passive sampling-based estimates of interstitial water concentrations indicated that SWNT reduced PCB bioavailability. Results from this study suggest that SWNT are a good adsorbent for PCBs and might be useful for remediation in the future once SWNT manufacturing technology improves and costs decrease.